2018
DOI: 10.1002/anie.201801001
|View full text |Cite
|
Sign up to set email alerts
|

Tunable Pentapeptide Self‐Assembled β‐Sheet Hydrogels

Abstract: Oligopeptide‐based supramolecular hydrogels hold promise in a range of applications. The gelation of these systems is hard to control, with minor alterations in the peptide sequence significantly influencing the self‐assembly process. We explored three pentapeptide sequences with different charge distributions and discovered that they formed robust, pH‐responsive hydrogels. By altering the concentration and charge distribution of the peptide sequence, the stiffness of the hydrogels could be tuned across two or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
76
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 105 publications
(81 citation statements)
references
References 44 publications
4
76
0
1
Order By: Relevance
“…A simple and robust pH‐responsive hydrogel was produced by Scherman and co‐workers, who reported the production of hydrogels formed from three pentapeptide sequences based on the amino acids Isoleucine (I) and Aspartate (D): IDIDI DDIII and DIID 96. Upon addition of HCl, the concentration and charge distribution of the peptide sequence was altered.…”
Section: Aqueous Stimuli‐responsive Materialsmentioning
confidence: 99%
“…A simple and robust pH‐responsive hydrogel was produced by Scherman and co‐workers, who reported the production of hydrogels formed from three pentapeptide sequences based on the amino acids Isoleucine (I) and Aspartate (D): IDIDI DDIII and DIID 96. Upon addition of HCl, the concentration and charge distribution of the peptide sequence was altered.…”
Section: Aqueous Stimuli‐responsive Materialsmentioning
confidence: 99%
“…Scherman et al explored and screened a pentapeptide hydrogel (IDIDI) with tunable morphology and mechanical properties produced through reassembly of the b-sheet interactions, which showed potential applications in delivery systems and tissue engineering. 29 The primary effect of physically cross-linked hydrogels is the formation of physical crosslinking points inside the gels. In 1993, Zhang et al 30 reported that a 16-residue peptide [(Ala-Glu-Ala-Glu-Ala-Lys-Ala-Lys) 2 ] (EAK16) could spontaneously assemble into a hydrogel structure in the presence of salt, which opened up the new eld of self-assembly technology of polypeptide molecules.…”
Section: Hong Liu Has Been Working As a Professor In Department Of Comentioning
confidence: 99%
“…Scherman's research focuses on dynamic supramolecular self‐assembly at interfaces though the application of macrocyclic host–guest chemistry. He has reported in Angewandte Chemie on pentapeptide self‐assembled β‐sheet hydrogels …”
Section: Awarded …mentioning
confidence: 99%